Music-like stimuli affect the emotional processing of words and facial expressions. (May 2021) - Ignacio, Daniel Andre; Gerkens, David R; Aguinaldo, Erick Ryan; Arch, Dina; Barajas, Ruben
The present study used the affective priming paradigm to understand interference and facilitation effects of cross-modal emotional interactions; specifically, the ability for five-chord progressions to affect processing efficiency of visual targets. Twenty-five-chord progressions were selected based on the degree that they fulfilled participants' automatically formulated expectations of how each musical sequence should sound. The current study is an extension of previous research that revealed the influence of music-like stimuli on the identification of valence in emotional words. The potential of music-like stimuli to affect emotional processing, as measured by the efficiency of valence categorization, was assessed across two experiments. Experiment 1 presented word-targets, whereas Experiment 2 presented facial expressions. The processing of words and faces primed with affectively congruent chord-progressions was facilitated, whereas the processing of words primed with affectively incongruent chord-progressions was not. Incongruent pairings with faces engendered interference effects and the second experiment revealed a predictive relationship between behavioral processing speed and self-ratings of anxiety. The processing of word-targets was compared to facial expressions in the presence and absence of music. The results suggest that short musical sequences influence individuals' emotional processing, which could inform intervention research into how to attenuate potential attention biases.